Analysis of cranial ultrasound images for newborn - Zhang, Qing; Zhou, Xihui (Frontiers in Neurology, 2023)
Introduction Neonatal cranial ultrasound plays an important role in the evaluation of neonatal brain development and related diseases. Methods This paper preliminarily explored the analysis and interpretation methods of neonatal brain ultrasound images, and applied the relevant medical image analysis methods to analyze the relevant neonatal brain ultrasound images in more detail. Results Compared with other types of imaging methods, ultrasound has its unique advantages and characteristics in such applications as neonatal head imaging. Discussion The analysis steps and schemes adopted in this paper have certain reference significance for the analysis of other neonatal brain pictures.